The cosmopolitan First Amendment : protecting transborder expressive and religious liberties / Timothy Zick, William & Mary Law School. - Zick, Timothy (Cambridge University Press, 2014)
We live in an interconnected world in which expressive and religious cultures increasingly commingle and collide. In a globalized and digitized era, we need to better understand the relationship between the First Amendment to the United States Constitution and international borders. This book focuses on the exercise and protection of cross-border and beyond-border expressive and religious liberties, and on the First Amendment's relationship to the world beyond US shores. It reveals a cosmopolitan First Amendment that protects cross-border conversation, facilitates the global spread of democratic principles, recognizes expressive and religious liberties regardless of location, is influential across the world, and encourages respectful engagement with the liberty regimes of other nations. The Cosmopolitan First Amendment is the product of historical, social, political, technological and legal developments. It examines the First Amendment's relationship to foreign travel, immigration, cross-border communication and association, religious activities that traverse international borders, conflicts among foreign and US speech and religious liberty models, and the conduct of international affairs and diplomacy.